Law and politics on export restrictions : WTO and beyond - Wu, Chien-Huei (Cambridge : Cambridge University Press, 2021)
Delving into export restrictive measures this book links the key areas of WTO law, public international law, investment and competition law to expose how and why WTO rules on export dimension are insufficient due to export bias; how public international law helps to justify their adoption or maintenance; and how investment and competition laws contribute to their regulation. Built on works on accession protocols and national security exceptions, this book goes beyond international trade law and looks into international political economy, competition and investment law. It contributes to debates in conceptualising public and private forms of export restrictions, appreciating the complementary nature of trade and competition law in disciplining them; capturing the dynamic between trade and investment policies for their effectuation and circumvention; and bridging trade law and public international law to better understand their impositions for political and diplomatic purposes with the invocation of the national security justification.
Introduction -- WTO rules on export restrictions -- Governing export restrictions : national security and international political economy -- Export restrictions in the global supply chain : investment and competition -- Conclusion : reconfiguring global supply chain in the post-COVID-19 era.
Title from publisher's bibliographic system (viewed on 09 Jul 2021).
Keywords: World Trade Organization; Export controls